PdCl2(bipy) complex - an efficient catalyst for Heck reaction in glycol-organic biphasic medium - Jagtap, Sangeeta Vijay; Deshpande, Raj Madhukar (Catalysis Today, 2008)
The Palladium complex PdCl2(bipy) (1) was found to be efficient in catalyzing the Heck reaction of aryl halides in a biphasic system comprising ethylene glycol along with an organic solvent. A proper tailoring of the organic phase ensured that the leaching of the catalyst to the organic phase was negligible. The catalyst was active for the Heck reaction of a number of olefins, aryl halides, in presence of organic and inorganic bases. The PdCl2(bipy) catalyst was stable and could be recycled for five times without any loss in activity and selectivity. A major advantage of this work is that unlike hitherto reported biphasic systems; it does not employ a water-soluble ligand to achieve biphasic catalysis. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biphasic catalysis; C-C coupling; Heck reaction; PdCl2(bipy) complex

Kinetics of the Heck reaction in biphasic organic-ethylene glycol medium - Jagtap, Sangeeta Vijay; Deshpande, Raj Madhukar (Reaction Kinetics Mechanisms and Catalysis, 2012)
PdCl2(bipy) was found to be an efficient and stable catalyst in biphasic medium (organic-glycol) for the Heck reaction. The kinetics of the Heck coupling of styrene with iodobenzene using the same catalyst was studied in a biphasic medium in a temperature range of 393-413 K. The rate was found to have a first order dependence tending to a fractional order, on the iodobenzene as well as catalyst concentration. The rate was found to have a complex dependence on the styrene concentration and passes through a maximum, showing typical substrate inhibition kinetics. The rate had a first order dependence on the base (morpholine) concentration. The trends observed for the influence of the different parameters on the activity of the catalyst are in agreement with the established mechanism for Heck reaction. An empirical rate model has been proposed to fit the observed rate data. The activation energy was found to be 72.91 kJ/mol. This is the first time that kinetic modeling of Heck reaction in a biphasic medium (organic-glycol) has been attempted.
Keywords: Biphasic catalysis; Heck reaction; kinetics; PdCl2(bipy) complex